Interface between gender and the COVID-19 induced work-from-home policy: evidence from a Zimbabwe University - Efiritha Chauraya (Inderscience Publishers, 2022)
The current study interrogated the interface between gender and the COVID-19 induced work-from-home policy as it identified manifestations of gender inequalities in the policy. The study was an instrumental case study of nine heterosexual lecturer-couples at a university in Zimbabwe. The couples, who were purposively sampled, were identified though snowballing. Telephone interviews were used to solicit data from the participants. Data was thematically analysed. A gender divide was registered in issues to do with work load while working from home and this, resultantly, led to a further divide on work productivity and satisfaction. Thus, the gender inequality and inequity in the policy contributed to the overall discrimination against female lecturers among other existing socio inequalities. The university was urged to make periodic check-ins on its female lecturers working from home just as a social support mechanism that may reduce burn out.